POTENCIAL DE Trichoderma spp. NATIVOS DO MATO GROSSO DO SUL COMO PROMOTOR DE CRESCIMENTO EM MUDAS FLORESTAIS - da Silva Pires, Valdirene; Fernandes Costa , Brenda; Caroline Pereira Jesus , Nielly; Gonçalves Mendonça , Cristiane (ANAIS DO ENIC, 2026)
-